EVALUATION OF SWEET POTATO (IPOMOEA BATATAS L.) PERFORMANCE AND SOILPROPERTIES UNDER TILLAGE METHODS AND POULTRY MANURE LEVELS - Agbede, T. M.; Adekiya, A. O. (Emirates Journal of Food and Agriculture, 2011)
Research study on the effect of tillage systems and application rate of poultry manure on sweet potato (Ipomoea batatas) in Alfisol of southwest Nigeria is lacking. Field trials were conducted in 2006, 2007 and 2008 cropping seasons on an Alfisol (Oxic Tropuldalf) at Owo in rainforest zone of southwest Nigeria. The trials consisted of the factorial combinations of two tillage methods (manual clearing and conventional tillage) and four manure levels (0, 5, 10 and 15 t/ha) arranged in a randomized complete block design and replicated three times. Conventional tillage alone (CTo) resulted in lower soil N, P, K, Ca, Mg and soil organic C and better leaf N, P, K, Ca and Mg concentrations, growth and yield of sweet potato compared with manually cleared (MCo) plots. The better performance of sweet potato under conventional tillage (CTo) was adduced to reduced bulk density. Bulk density was negatively correlated with yield. Conventional tillage alone (CTo) improves sweet potato tuber yield by 62, 55 and 42% in 2006, 2007 and 2008, respectively compared with manual clearing alone (MCo). In both the manually cleared and conventionally tilled plots, soil organic C, N, P, K, Ca, Mg and water content increased with amount of poultry manure, while soil pH, bulk density and temperature were reduced. Yields given by 5, 10 and 15 t/ha poultry manure were not significantly different under both manually cleared and conventionally tilled treatments. Conventional tillage plus 5 t/ha poultry manure (CT+5 PM) produced the highest overall yield. Compared with manual clearing alone (MCo) and conventional tillage alone (CTo), conventional tillage plus 5 t/ha poultry manure (CT+5 PM) improved tuber yield of sweet potato by 117 and 43%, respectively. Therefore the use of 5 t/ha poultry manure with conventional tillage is recommended for sweet potato production on an Alfisol of southwest Nigeria.